(untitled) (International Conference on Education, Psychology and Humanities, 2026)
Language learning is not only about acquiring grammar rules and vocabulary; it also involves understanding the cultural and moral values embedded in a language. Proverbs, as short and meaningful sayings, provide rich insights into the traditions, beliefs, and societal norms of a community. Integrating proverbs into English teaching offers learners an opportunity to develop linguistic competence while simultaneously appreciating cross-cultural wisdom. In particular, Uzbek and Afghan proverbs are rich in moral, philosophical, and practical knowledge, making them valuable resources in the English language classroom.